Designing an English oral achievement test for second year students at Bac Ninh Physical Education and Sports University. M.A Thesis Linguistics: 60 141 - Dương, Thị Hoà (University of Languages and International Studies, 2017)
The purpose for this study is designing an English oral achievement test for second year students at Bac Ninh UPES. In the first part of the study, the introduction is presented. The literature review of language testing, achievement test, some suggestions to improve the current English test and some components for oral achievement test are shown in the second part. The third part gives conclusions to the research questions. Two sets of questionnaires were conducted to find out the students’ attitude, English teachers’ opinions and their suggestions for designing an English oral achievement test. Basing on the results from the collected data, the researcher has designed a proposed English oral achievement test for the second year students at Bac Ninh UPES. The author hopes that this study would be helpful for the teachers and students at Bac Ninh UPES. M.A Thesis English Teaching Methodology -- University of Languages and International studies. Vietnam National University, Hanoi, 2011